AB0294 Treatment modes in rheumatoid arthritis: factors influencing patient preference. (12th June 2018) - Taylor, P.C.; Betteridge, N.; Brown, T.M.; Woolcott, J.; Kivitz, A.J.; Zerbini, C.; Whalley, D.; Olayinka-Amao, O.; Chen, C.; Dahl, P.; Ponce de Leon, D.; Gruben, D.; et al.
Abstract : Background: Little in-depth qualitative research has been conducted to investigate reasons for rheumatoid arthritis (RA) patient (pt) preferences for different modes of treatment administration. An understanding of pt preference can help physicians personalise therapy recommendations. Objectives: To describe potential RA pt preferences for RA treatment modes and reasons for these preferences. Methods: Pt demographic information was obtained at screening alongside qualitative interviews conducted using a semi-structured interview guide among adult RA pts in the US, UK, France, Germany, Italy, Spain, Switzerland and Brazil who were currently taking a DMARD (biologic or non-biologic). A 100-point allocation task was used to evaluate the strength of preference (0–100; 100=strong) across 4 treatment modes: oral (OR; once daily), self-injection (SI; weekly), clinic-injection (CI; weekly) and infusion (INF; monthly). Transcripts were developed in English; ATLAS.ti software (v7.5) was used for qualitative coding and analysis. Results: 100 interviews (30 US; 10 in each of 7 other countries) were conducted (female: 75.0%; mean age: 53.9 years; mean time since diagnosis: 11.6 years). Current RA medication mode included OR (60.0%), injection (57.0%) and INF (14.0%); 79.0% and 37.0% of pts had experience with injection and INF medications, respectively; 31.0% of pts were taking a combination of biologic and non-biologic DMARDs. Among the 4 treatment modes, OR was allocated the highest mean (standard deviation [SD]) preference points (47.3 [33.1]) and the greatest percentage of pts with a 1st choice rank (57.0%); this was followed by SI (29.7 [27.7]; 29.0%), INF (15.4 [24.6]; 16.0%) and CI (7.5 [14.1]; 2.0%). Preferences by country suggested that the mean points allocated to OR were greater in the US vs other countries. Across all pts and treatment modes, 56.0% of pts had a 'strong' 1st choice preference (ie, a pt allocation ≥the mean pts across the 1st ranked choices [70]); of these pts, the majority chose OR (62.5%; SI: 23.2%; INF: 10.7%; CI: 3.6%). Speed of administration was among the most common reasons for choosing OR or SI as a 1st choice, together with ease of administration (OR) and frequency of dosing (SI; table 1). Difficulty remembering was the most common reason for not choosing OR and avoidance of pain was the most common reason for not choosing SI as a 1st choice. Conclusions: More pts preferred OR as an RA treatment mode, followed by SI. Rationales for preference included ease of use, concerns about drug interactions, dosing frequency, feelings of control and avoidance of pain and needles. While 56.0% of pts felt strongly about their 1st choice preference, nearly half did not and may be receptive to and benefit from discussions with their healthcare professional and/or pt support groups about RA treatment mode options. Acknowledgements: Study sponsored by Pfizer Inc. Editorial support was provided by C Viegelmann of CMC and funded by Pfizer Inc. Disclosure of Interest: P. Taylor Grant/research support from: Celgene, Eli Lilly, UCB Pharma, Consultant for: AbbVie, Biogen, Eli Lilly, Galapagos, Janssen, Merck, Pfizer Inc, Roche, Sandoz, Sanofi, UCB Pharma, N. Betteridge Consultant for: Eli Lilly, Grunenthal, Janssen, Pfizer Inc, Roche, Sanofi Genzyme, T. M. Brown Consultant for: Pfizer Inc, Employee of: RTI-HS, J. Woolcott Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, A. Kivitz Consultant for: AbbVie, Celgene, Genentech, Genzyme, Janssen, Merck, Novartis, Pfizer Inc, Sanofi, UCB, Speakers bureau: AbbVie, Celgene, Genentech, Genzyme, Janssen, Merck, Novartis, Pfizer Inc, Sanofi, UCB, C. Zerbini Grant/research support from: Amgen, Celltrion, Eli Lilly, GSK, Merck, Novartis, Pfizer Inc, Sanofi, Consultant for: Eli Lilly, Pfizer Inc, Sanofi, D. Whalley Consultant for: Pfizer Inc, Employee of: RTI-HS, O. Olayinka-Amao Consultant for: Pfizer Inc, Employee of: RTI-HS, C. Chen Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, P. Dahl Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, D. Ponce de Leon Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, D. Gruben Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, L. Fallon Shareholder of: Pfizer Inc, Employee of: Pfizer Inc